The acute effects of various dynamic stretching exercises on jump performance and range of motion - Mustafa Savaşan; Yeliz Pınar; Salih Pınar (Sport TK)
This study aimed to investigate the acute effects of different dynamic stretching (DS) protocols on vertical jump performance and range of motion (ROM). Thirty healthy male participants, with an average age of 23.48 years, body weight of 76.90 kg, and height of 181.87 cm, who had engaged in recreational exercise for at least two years, participated voluntarily. A "cross-controlled randomized" experimental design was utilized to assess four distinct DS protocols: a-DS at 100 bpm for 30", b-DS at 100 bpm for 75" s, c-DS at 150 bpm for 30", and d-DS at 150 bpm for 75". Acute ROM was measured using the Passive Straight Leg Raise Test (PSLR), while jump performance was assessed via countermovement jump (CMJ). Data were analyzed using repeated measures ANOVA and paired samples T-tests with significance set at p<.05. All four DS techniques significantly increased angles measured by PSLR following application (p <.05). CMJ values also showed significant improvements in both groups subjected to the shorter protocols lasting 30"at either tempo (p <.05). Consideration should be given to application duration and tempo when planning DS exercises, as structured warm-up routines can enhance flexibility and optimize athletic performance.